NAKED BARLEY: ORIGIN, DISTRIBUTION, AND PROSPECTS OF UTILISATION - A. V. Zhelesnov; T. V. Kukoeva; N. B. Zheleznova (Вавиловский журнал генетики и селекции)
This article presents one of the most interesting forms of barley (Hordeum vulgare L.) and characterizes its chemical composition and productivity. It is shown that modern methods of molecular biology provide much deeper insight into the domestication history and diversity of naked barley than common methods of population genetics. The importance of selection for increasing naked barley yield and, as a consequence, for expanding its cultivation area is emphasized. Methods and directions of breeding are considered in this respect. Germplasm from South-East Asia, China, Japan, and other regions is of special significance for naked barley selection. That is why great attention should be paid to its preservation.